Hubungan Pengetahuan Dan Sikap Terhadap Tindakan Pencegahan Covid 19 Pada Masyarakat Di Rt 02/ Rw 02 Kelurahan Andalas Wilayah Kerja Puskesmas Andalas Kota Padang - Ira Sri Budiarti; Eliwarti; Aminah Siregar (Jurnal Amanah Kesehatan, 2022)
Based on a report from the padang city health office in 2022, it was stated that the andalas health centre was one of the health centers with the highest number of covid 19 incidents. The purpose of this study was to determine the relationship betwen knowledge and attitudes towards covid 19 prevention measures in the community in RT 02/RW 02 Andalas Village, Working Area Of Andalas Health Centre, Padang City.This type of research is deskriptive analytical using a cross sectional design. This research was conducted in RT 02/RW 02. Reasearch and data collection was carried out from march 2022 to july 2022, with a population of 121 and a sample of 55 respondents. The sampling technique used proportional random sampling. The data obtained were analized univariately with a frequency distribution and bivariate with statistical tests Chi Square.The result of univariate study obtained knowledge (47,3%), attitudes (43,6 %) and preventive measures for covid 19 (54,5%). Bivariate research results based on statistical tests it was found that there was a significant relationship between knowledge (p=0,017) and no mean relationship between attitude (p=1,00) with covid 19 prevention measures in the community in RT 02/RW 02 Andalas Village, Working Area Of Andalas Health Centre, Padang City. Based on the research above, it can be concluded that preventive measures for covid 19 are influenced by public knowledge. It is recomended to the health centre to provide specific, valid and targeted knowledge in order to improve community prevention measures against Covid 19 infection.